Fulfilment National Standard Education toward Achievement of Critical Thinking Ability and Science Process Skill in Indonesia - Pamungkas, Zakaria Sandy; Aminah, Nonoh Siti; Nurosyid, Fahru (American Journal of Social Sciences and Humanities, 2019)
This study aims to evaluate the fulfillment of national standards of education, and knowing the achievement of students’ critical thinking ability and science process skills. This research uses descriptive research. The subject of this research is a physics teacher and student of grade XI IPA 4 in SMAN 2 Surakarta. Data collection method are used methods of observation, questionnaires, documentation, and interviews. Data analysis techniques are using quantitative descriptive analysis and qualitative descriptive analysis. The results showed that content standard and process standard have not been fully implemented in school with the percentage of fulfillment of process standard in an aspect of planning 85%, implementation aspect 53%, and evaluation aspect 80%. This leads to the achievement of critical thinking ability and the science process skills of learners are in a low category. The average percentage achievement of students' critical thinking ability is 31.4% and the average percentage achievement of students' science process skill is 27.6%.